2006
DOI: 10.1128/jb.00942-06
|View full text |Cite
|
Sign up to set email alerts
|

Structural Organization and Functional Properties of Miniature DNA Insertion Sequences in Yersiniae

Abstract: YPALs (Yersinia palindromic sequences) are miniature DNA insertions scattered along the chromosomes of yersiniae. The spread of these intergenic repeats likely occurred via transposition, as suggested by the presence of target site duplications at their termini and the identification of syntenic chromosomal regions which differ in the presence/absence of YPAL DNA among Yersinia strains. YPALs tend to be inserted closely downstream from the stop codon of flanking genes, and many YPAL targets overlap rho-indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…Another class of mobile repeat units of approximately 167-bp, Yersinia palindromic sequences (YPAL) and termed RU-2 in this study, was recently reported to be present in Yersinia species (De Gregorio et al 2006). Independently, we also detected this class of repeat unit, which has an approximate 168-bp chain length and is found in 60 different intergenic regions of the Yersinia pestis chromosome.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…Another class of mobile repeat units of approximately 167-bp, Yersinia palindromic sequences (YPAL) and termed RU-2 in this study, was recently reported to be present in Yersinia species (De Gregorio et al 2006). Independently, we also detected this class of repeat unit, which has an approximate 168-bp chain length and is found in 60 different intergenic regions of the Yersinia pestis chromosome.…”
Section: Introductionmentioning
confidence: 67%
“…While scanning genomic sequences in Yersinia species for the E. coli non-coding RNA gene itsR (Vogel et al 2004), a 168-bp sequence was found which is related to a previously described 167-bp repeat (De Gregorio et al 2006). The nucleotide sequence of a representative repeat element from the Y. pestis CO92 genome (termed RU-2) and its location in the genome are shown in Table 1b.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…All strains were routinely grown in brain heart infusion at 37 1C, except for the environmental strains (LMG959, LMG10871, LMG10879, LMG11104, and LMG11108) which were grown at 30 1C. Genomic DNA was extracted as described (De Gregorio et al, 2006). PCR amplifications.…”
Section: Bacterial Strains and Genomic Dna Extractionmentioning
confidence: 99%